Misinformation - Jing Zeng; Scott Babwah Brennen (Internet Policy Review, 2023)
This article delves into the diverse and complex nature of conceptualising misinformation as an object of research, highlighting the interdisciplinary scholarship in this field that results in varied and sometimes conflicting definitions. While a singular theory of misinformation is neither feasible nor desirable, the article argues for the importance of greater conceptual comprehensiveness in empirical research. Without a comprehensive and comparable definition of misinformation, accurately measuring the problem's scale becomes challenging, potentially leading to underestimation or overhyping of its impact and misguided interventions. Furthermore, addressing the growing demand for countering misinformation in public and policy-making domains necessitates a nuanced understanding of its roots in cultural, sociopolitical, and technological systems. Existing academic discussions on remedies often adopt a Western-centric perspective, overlooking unique power dynamics in non-democratic and non-Western contexts. Therefore, future discussions on countermeasures should prioritise the Global South and other understudied contexts, avoiding one-size-fits-all solutions.